APPLICATION OF POLYVITAMINS AMONG CHILDREN - I.A. Gromov; V.A. Barannik; R.M. Torshkhoeva; L.S. Namazova (Педиатрическая фармакология)
For the normal vital activity of a person, it is necessary to have a sufficient intake of the vitamins, which is not always possible in the event of the balanced food ration. Neither of the products contains them to the extent so sufficient for the satisfaction of the physiological needs. The article gives causes and consequences of the vitamin deficiency, as well as the strategy (therapeutic and preventive) of its correction. The authors demonstrate the efficiency and safety findings of the vitamin and mineral complex applied for the preventive purposes.Key words: vitamins, physiological need, vitamin deficiency, prevention, treatment, children.